Carl Van Vechten and the Harlem Renaissance : a portrait in black and white - Bernard, Emily, 1967- (Yale University Press, 2012)
"By the time of his death in 1964, Carl Van Vechten had been a far-sighted journalist, a best-selling novelist, a consummate host, an exhaustive archivist, a prescient photographer, and a Negrophile bar non. A white man with an abiding passion for blackness."-- Resumé vydavatele